Analisis kesulitan mahasiswa dalam pembuktian matematis pada mata kuliah analisis real - Anwar Mutaqin; Syamsuri Syamsuri; Aan Hendrayana (Universitas Sultan Ageng Tirtayasa, 2022)
This study was conducted to determine and analyze the learning obstacles of students in constructing proof on Real Analysis course. Samples are undergraduate at Departement of Mathematics Education is being contracted Real Analysis course of two state universities, namely the University Pendidikan Indonesia (UPI) and the University of Sultan Ageng Tirtayasa (Untirta). Data were collected through structured interviews. Students are given a number of evidentiary matter then conducted interviews to determine the errors that arise when developing a mathematical proof. The results showed that student difficulties when preparing evidence are: 1) start the proof, 2) definitions and axioms, 3) the form of algebraic manipulation, 4) integrate the definitions and / or theorems in a proof structure, 5) choose the way of proof, 6) choose the theorem to construct proof, 7) construct their own examples and counter examples.